Identification of the Redox Reaction Between CuSO₄ and Zn Through Visual Observation in Basic Chemistry - Igoy Arya Bimo; Rendra Lebdoyono; Luluk Alifia; Raida Amelia Ifadah (ALCHEMY:Journal of Chemistry, 2026)
Oxidation–reduction (redox) reactions are important chemical processes characterized by the transfer of electrons between substances and changes in oxidation numbers. This study aims to identify the occurrence of a redox reaction between copper (II) sulfate (CuSO₄) ions and zinc (Zn) metal through observations of changes in solution color, the formation of copper deposits, and physical changes in the zinc metal. The experiment was conducted descriptively using three variations of Zn mass (0.1, 0.2, and 0.3 grams) and was compared with a negative control using ZnSO₄. In the negative control sample, only the physical dissolution of ZnSO₄ occurred without the formation of copper deposits, indicating the absence of a redox reaction. In contrast, in samples using pure Zn metal, the redox reaction proceeded spontaneously, indicated by the fading of the blue color of the CuSO₄ solution and the formation of copper deposits ranging from reddish-brown to dark on the surface of the zinc. Variations in Zn mass affected the rate of Cu²⁺ reduction, where larger metal masses showed a slower initial reaction but still produced copper deposits at the end of the reaction period. This study confirms that Zn acts as the reducing agent and Cu²⁺ serves as the oxidizing agent in the CuSO₄–Zn redox system.